Self-employment and social risk management: comparing Germany and the United Kingdom - Schulze Buschoff, Karin (Berlin, 2007)
"In the past decades self-employment has gained importance in both countries Germany and the United Kingdom. In particular the proportion of solo-self-employment shows an increasing trend. This development has created new challenges for social risk management strategies. It raises the question of whether and to what extent the national social security systems for the self-employed are working and are capable of dealing with the new situation. To answer this question, the paper evaluates Germany´s and the United Kingdom´s legislation on the social protection of self-employment. Furthermore the collective representation of interests of the self-employed e.g. through trade unions is described. Finally, private provisions for retirement are outlined as an example for individual risk management strategies of the self-employed."